Surgery outcomes and functionality in patients with cervical spondylotic myelopathy - Azimi, Parisa; Shahzadi, Sohrab; Mohammadi, Hassan Reza; Alizadeh, Pooyan; Shahzadi, Andia (International Clinical Neuroscience Journal, 2014)
Purpose: This study investigated functionality statues and surgical outcome of patients with cervical spondylotic myelopathy (CSM) contains cervical herniated disc (CHD) and cervical spinal stenosis (CSS) based on the Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ). Methods: This was a prospective clinical study a sample of cases with CSM. Patient’s functionality statues and surgical outcome were evaluated based on JOACMEQ scores at two points in time: pre- and postoperative assessments. Results: In all 87 patients were completed the JOACMEQ measure. The mean age of patients was 50.3 (SD=10.2) years. The mean clinical follow-up was 12 months (range 7-37 months). Statistically difference between was observed pre- and postoperative indicating improvements on the outcomes and functionality in all subscales (P < 0.001). However, there was no significant difference between patients with CSM and CHD. Conclusion: The findings suggest that surgery is an efficacious procedure for the treatment of CSM and the functionality statues as measured by the JOACMEQ are higher than prior to surgery.